Case report: Urgent surgical management of pediatric clear cell sarcoma of the kidney with atrial obstruction - Varga, Alexandra; Bogáts, Gábor; Rácz, Katalin; Kovács, Tamás (Frontiers in Pediatrics, 2022)
Clear cell sarcoma of the kidney is an uncommon renal neoplasm of childhood. Intracaval or cavoatrial thrombotic progression is extremely rare and mostly asymptomatic, treated with neoadjuvant therapy followed by surgery. However, in an unstable patient acute radical surgical intervention is the treatment of choice. We present a 2-year-old girl diagnosed with a large left kidney tumor and acute cardiac decompensation via cavoatrial thrombotic progression. Urgent radical nephrectomy and tumor thrombus removal was performed using atriotomy and inferior vena cava endarterectomy under cardiopulmonary bypass. Histopathology revealed clear cell sarcoma of the kidney. The patient is tumor-free on nine years follow-up.